Meningkatkan Kemampuan Spasial Siswa Kelas VII SMPN 4 Taliwang melalui Aplikasi Android Virtual Reality Mathematics Berbantuan Google Cardboard - Kanti Warih Ade Indriani (Indonesian Publication Center, 2020)
Students need visualization media in bridging abstract concepts of geometry into contextual understanding. For example, is the virtual reality mathematics application for android (VR math) for teaching geometry. It’s supported by a media called google cardboard, as an output device in applying VR technology. This study aim is to improve students' spatial ability. This research is a classroom action research with two cycles. Where each cycle consists of 4 stages are planning, action, observation and reflection. The research subjects were 24 students of 7th grade at SMPN 4 Taliwang. Data sources obtained from the learning process observation and tests. The instruments used were observation sheets and tests. After the data are collected, analyzed then concluded descriptively. The results of the study are the achievement of score from the first cycle to the second is 79 (adequate category) to 89.5 (good category). It showed that the score progress has reached the performance indicator. For students' spatial ability, in the pre-cycle included in lack category (34 scores). After given action study, it reached to score 56 (adequate category) in the first cycle to 66,4 (good category) in the second cycle. It's mean the achievement had reached the performance indicator. The research concludes that the Android VR application is effective for learning mathematics, especially in spatial ability. Research recommendations are mathematics teachers should master ICT so that it can be integrated into learning to create interesting, fun, and challenging mathematics learning.